PENGEMBANGAN COOKIES BERBASIS TEPUNG KACANG HIJAU DAN LABU KUNING UNTUK BALITA STUNTING - Hamumeha, Abigail Diwa; Sulaeman, Agus; Isdiany, Nitta; Fitria, Mona (Jurnal Gizi dan Dietetik, 2025)
Globally, approximately 149.2 million (22.2%) children under five years of age suffer from stunting. In Indonesia, the 2018 Basic Health Research (Riskesdas) reported a stunting prevalence of 30.8%. One nutrition intervention approach is the provision of supplementary foods utilizing local ingredients, including cookies. Cookies made from a combination of mung bean flour and pumpkin flour have the potential to serve as a high-protein and high-calcium snack for stunted toddlers. This study aimed to evaluate the effect of different flour proportions on the organoleptic properties and nutritional content of the cookies. An experimental design was applied using three formulations: F1 (50%:50%), F2 (60%:40%), and F3 (70%:30%). Organoleptic evaluation was conducted using a hedonic test involving 30 semi-trained panelists. The results showed no significant differences in color, aroma, taste, texture, and overall acceptability among the formulations (p > 0.05). Formula F2 was identified as the most preferred, with an overall score of 5.63. Laboratory analysis of the selected formula revealed a protein content of 11.2 g and a calcium content of 254 mg per 100 g. Further studies are recommended to improve crispness and conduct proximate analysis to enhance the accuracy of nutritional data.